The Impact of Optimal Glycemic Control on Tuberculosis Treatment Outcomes in Patients With Diabetes Mellitus: Systematic Review and Meta-Analysis - Li Zhao; Feng Gao; Chunlan Zheng; Xuezhi Sun (JMIR Publications, 2024)
BackgroundDiabetes mellitus (DM) increases the risk of developing tuberculosis (TB), and optimal glycemic control has been shown to reduce the risk of complications and improve the TB treatment outcomes in patients with DM. ObjectiveThis study aims to investigate the role of glycemic control in improving TB treatment outcomes among patients with DM. MethodsMEDLINE, Embase, and the Cochrane Central Register of Controlled Trials databases were searched for randomized controlled trials (RCTs) assessing the impact of oral glycemic control in patients with TB who have DM. Outcomes of interest were radiological findings, treatment success, sputum positivity, and mortality. Evaluations were reported as risk ratios (RRs) with 95% CIs using weighted random-effects models. ResultsThe analysis included 6919 patients from 7 observational studies. Our meta-analysis showed significant differences between patients with optimal glycemic control and those with poor glycemic control with regard to improved treatment outcomes (RR 1.13, 95% CI 1.02-1.25; P=.02; I²=65%), reduced sputum positivity (RR 0.23, 95% CI 0.09-0.61; P=.003; I²=66%), and fewer cavitary lesions (RR 0.59, 95% CI 0.51-0.68; P<.001; I²=0%) in radiological findings. There was no significant difference between the 2 groups in terms of mortality (RR 0.57, 95% CI 0.22-1.49; P=.25; I²=0%), multilobar involvement (RR 0.57, 95% CI 0.22-1.49; P=.25; I²=0%) on radiologic examination, and upper lobe (RR 0.94, 95% CI 0.76-1.17; P=.58; I²=0%) and lower lobe (RR 1.05, 95% CI 0.48-2.30; P=.91; I²=75%) involvement on radiologic examination. ConclusionsWe concluded that optimal glycemic control is crucial for reducing susceptibility, minimizing complications, and improving treatment outcomes in patients with TB with DM. Emphasizing effective health management and health care strategies are essential in achieving this control. Integrating comprehensive care among patients with TB with DM will enhance patient outcomes and alleviate the burden of disease in this population. Trial RegistrationPROSPERO CRD42023427362; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=427362